Hot-filament plasma enhanced chemical vapour deposition of transfer-free graphene using nickel catalyst / Maisara Othman - Maisara , Othman (2018)
The synthesis and characterization of transfer-free graphene using a home-built plasma enhanced chemical vapour deposition (PECVD) system were studied in this research. Most of the graphene growth using the CVD technique require a metal surface and an additional lift-off step to transfer the graphene from the metal surface. The structures of the graphene could be damaged during the transferring process, leading to a performance which is far below the theoretical value in reality. Nevertheless, CVD technique can produce graphene with a large area that has vital roles in the industry and engineering. Its potential roles have led to the fabrication of transfer-free graphene reported by some existing studies but the commercialization of this technique remains challenging due to the complexity of the method. In this study, the transfer-free graphene was deposited on the silicon dioxide (SiO2) substrate at a relatively low temperature using the nickel (Ni) thin films. The Ni layer was used as a catalyst to assist the formation of graphene at the Ni-substrate interface. Prior to the deposition of graphene, a thin Ni film was deposited onto the SiO2 substrate using the sputtering technique. The morphology, thickness, and grain size of the Ni films were shown to be dependent on the Ni target to substrate distance. Furthermore, the structure, morphology, and chemical bonding of the transfer-free graphene were found to be strongly dependent on the thickness and the grain size of the Ni films. The grain size was dependent on the Ni thickness, which had an impact on the Ni grain boundaries. The grain boundary acted as the nucleation site for the carbon atom to diffuse through the Ni. The formation of the transfer-free film shifted from carbon to graphene when the Ni thickness was increased. An optimized Ni thickness resulted in a more ordered graphene with lesser defect. Furthermore, the addition of a hot-filament to the PECVD system further improved the quality of the transfer-free graphene under the same deposition condition. This is because the Ni catalyst showed better catalytic effects during graphene deposition using the hot-filament assisted PECVD as compared to the simple PECVD. The thermal effect promoted the formation of a less defective graphene with a more ordered structure, which could be achieved by larger Ni grain size and grains boundaries. The resulting transfer-free graphene films were investigated for their structural, chemical bonding and morphology. Deposition time strongly influenced the number of graphene layers and structural ordering. The graphene film shifted from multilayer towards bilayer graphene with lower defects when the deposition time was decreased by using the optimum parameters from the above studies, the highest quality transfer-free graphene was obtained by optimizing the substrate temperature. Decreasing the substrate temperature had increased the number of graphene layer and resulted in a highly defective graphene. The optimized substrate temperature for bilayer graphene growth was 400C at deposition time of 1 minute. The formation of defects due to a large distribution of non-perfect hexagonal graphene rings had led to a high inclusion of hydroxyl groups and oxygen, vacancy defects and ultra-long defective edges which subsequently affected the wettability and the magnetic properties of the graphene films.